Persediaan Barang Berbasis Web Pada Toko Nivico - Liyono, Alvin; M.Riza Pahlevi; Masgo (LPPM Universitas Dinamika Bangsa, 2025)
Technological developments, especially in the computer sector, have made inventory management an important aspect of running a business, especially retail stores. Nivico Shop is an electronics shop in Jambi that sells various kinds of electronic goods such as light bulbs, electrical cables and so on. The process of recording and monitoring inventory at the Nivico Store is still done manually, namely using books and notes. This method has several weaknesses, such as the possibility of recording errors, difficulty in obtaining the latest inventory reports, and the time required to update the data. In addition, limited information accessibility makes it difficult for owners and staff to make the right decisions regarding the procurement and sale of goods. With increasing market demand and intense competition, an information system is needed that can help Nivico Stores manage inventory more effectively. With this web-based inventory system, it is hoped that it can overcome problems in carrying out the data recording process at the Nivico Store.